A Rigorous Stylistic Analysis of My Chemical Romance’s "Disenchanted": A Leech and Short Approach to the Lexico-Grammatical Construction of Disillusionment - Reyhan Habib Akbar; Evaness Jocelym; Rahmadsyah Rangkuti (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2026)
This study investigates the linguistic and stylistic architecture of the song "Disenchanted" by the alternative rock band My Chemical Romance, utilizing the comprehensive framework proposed by Geoffrey Leech and Michael Short (1981/2007). While contemporary musicology frequently prioritizes acoustic performance, this paper treats modern lyrical texts as autonomous literary discourse. Employing a bottom-up methodology, the text is analyzed across six distinct linguistic strata: lexical choices, grammatical structures, figurative language, foregrounding mechanisms, phonological patterns, and cohesive devices. The empirical findings reveal a systematic reliance on stative and mental predicates (75% of total verbs) over dynamic actions, a calculated second-person pronominal dominance (50%) that serves as an identity-distancing tool, and striking semantic deviations that flatten human suffering into a mundane, failed theatrical production. Phonologically, dense clusters of sibilance create a cynical, whispering atmosphere that undercuts the typical energy of a rock anthem. Ultimately, this study demonstrates that the emotional resonance of 2000s alternative rock is a meticulously patterned linguistic construct, proving that contemporary popular lyrics possess the structural complexity to warrant rigorous stylistic inquiry.